2018
DOI: 10.1111/jmft.12326
|View full text |Cite
|
Sign up to set email alerts
|

Couple Differentiation: Mediator or Moderator of Depressive Symptoms and Relationship Satisfaction?

Abstract: The purpose of this investigation was to determine whether differentiation at the couple level would act as a moderator or a mediator in the association between marital satisfaction and depressive symptoms over time. In a sample of 412 couples, a latent profile analysis was performed to determine how couple differentiation scores were clustered. An Actor/Partner Interdependence Model was then estimated via a group comparison procedure in structural equation modeling. There was no evidence of a moderating effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
1
14
0
1
Order By: Relevance
“…For example, perhaps as differentiation, and therefore an ability to experience emotion and simultaneously make rational decisions, increases, so also would increase the capacity to be self‐directed in selecting a partner, regardless of differentiation level. Ultimately, given albeit small levels of significant similarity found in this study, a relatively high percentage of similarity found in other research that is couple centered (Bartle‐Haring et al., ), and support found for other BFST assumptions such as stability over time, Bowen's theory of similarity and BFST deserves further examination.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…For example, perhaps as differentiation, and therefore an ability to experience emotion and simultaneously make rational decisions, increases, so also would increase the capacity to be self‐directed in selecting a partner, regardless of differentiation level. Ultimately, given albeit small levels of significant similarity found in this study, a relatively high percentage of similarity found in other research that is couple centered (Bartle‐Haring et al., ), and support found for other BFST assumptions such as stability over time, Bowen's theory of similarity and BFST deserves further examination.…”
Section: Discussionsupporting
confidence: 70%
“…Overall however, results of this study are comparable to results from previous studies that do not offer strong support for Bowen's similarity hypothesis. This was surprising given that recent research that utilized a more couple‐centered approach found much higher levels of similarity using the same data set (Bartle‐Haring et al., ).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…It also offers five possible response options for the response, allowing one to obtain a self-report measure that assesses family differentiation, taking into consideration, on the one hand, ongoing emotional connectedness (support, involvement, personal relationship) and, on the other hand, separateness (autonomy, uniqueness, freedom of personal expression). Nevertheless, this scale does not address communication directly and, as a result, is more closely related to the evaluation of other aspects such as couple relationship satisfaction (Bartle-Haring, Ferriby, & Day, 2018;Lampis, Cataudella, Busonera, & Skowron, 2017;Muraru & Turliuc, 2012).…”
Section: Introductionmentioning
confidence: 99%